Efektivitas Program Sekolah Ramah Anak dalam Penguatan Iklim Inklusi di Sekolah Dasar: Systematic Literature Review - Wiji Listiyani; Liftiah Liftiah; Ali Formen (Universitas Muhammadiyah Metro, 2026)
Inclusive education requires a safe, supportive, and non-discriminatory school environment that can accommodate the diverse needs of all students, including children with special needs. The Child-Friendly School program, known in Indonesia as Sekolah Ramah Anak (SRA), is designed to create an educational environment that protects children’s rights, promotes participation, and supports inclusive learning practices. This study aimed to systematically analyze the effectiveness of SRA programs in strengthening inclusive climate in elementary schools, particularly in relation to students with special needs. A systematic literature review was conducted following the PRISMA 2020 guidelines. The review analyzed 27 scientific articles indexed in SINTA and Scopus and published between 2021 and 2026. The selected studies were examined through thematic synthesis to identify implementation patterns, benefits, challenges, and supporting factors related to SRA and inclusive education. The findings indicate that SRA programs contribute positively to inclusive education by improving school accessibility, strengthening teacher competence, enhancing students’ social interaction, reducing discriminatory practices, and creating safer and more supportive learning environments. However, several challenges remain, including limited infrastructure, insufficient trained teachers, weak policy implementation, lack of adaptive learning resources, and limited cross-sector collaboration. These findings suggest that SRA programs can serve as an important strategy for strengthening inclusive climate in elementary schools, but their effectiveness depends on systemic support, policy consistency, school readiness, and collaboration among teachers, school leaders, parents, communities, and policymakers. This study provides practical implications for elementary schools and education stakeholders in developing child-friendly and inclusive school systems that ensure equal learning opportunities for all students.